Socio-spatial adaptation in the food delivery system during the first stages of the Covid-19 pandemic in Guadalajara, Jalisco - Verduzco Chávez, Basilio; Valenzuela Varela, María Basilia (Acta Universitaria, 2022)
Focusing events are associated with opportunities for innovation and transformation of social practices. Socio-spatial adaptation processes induced by these events are a relevant issue due to theoretical and public policy reasons. This article analyzes the growth of food delivery services during the early stages of the Covid-19 pandemic and the socio-spatial adaptation observed in Guadalajara, Jalisco. Based on evidence generated through semi-structured interviews with food deliverers in the Providencia area, the study identifies four dominant socio-spatial adaptation strategies. Workers used them to adapt to the pandemic in a context of systemic problems of social and urban inequality, social distancing policies, and increased occupational hazards, while digital platforms gained legitimacy and pushed for service diversification.